BULLYING AMONG TEACHERS: PSYCHOLOGICAL FACTORS AND SOCIAL IMPACTS (Conferencea, 2024)
This article is devoted to the study of psychological factors and social influences of bullying among teachers. Bullying can create a negative atmosphere in the pedagogical team, reduce teachers' motivation for work, and lead to increased conflicts between team members. This article analyzes the main psychological factors of bullying as low self-esteem, mutual competition, stress at work, and lack of social adaptation in communication. The article also discusses the impact of social influences, including informal groups within the team, organizational culture, and management styles on bullying. Effective measures are proposed to prevent bullying and create a positive team environment, including psychological support and training programs. This study also includes practical recommendations aimed at creating a stable and supportive environment in the pedagogical team.